1997
DOI: 10.1017/s0022112096003916
|View full text |Cite
|
Sign up to set email alerts
|

Instability of a spatially developing liquid sheet

Abstract: The linear stability of an inviscid two-dimensional liquid sheet falling under gravity in a still gas is studied by analysing the asymptotic behaviour of a localized perturbation (wave-packet solution to the initial value problem). Unlike previous papers the effect of gravity is fully taken into account by introducing a slow length scale which allows the flow to be considered slightly non-parallel. A multiple-scale approach is developed and the dispersion relations for both the sinuous and varicose dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 20 publications
4
25
0
Order By: Relevance
“…It was shown by Crapper et al [12] that viscosity does not influence the initial stages of wave development, whilst Lin et al [13] showed that the critical Weber number does not depend on the liquid-gas density ratio or the Reynolds number. [14] provide an explanation of the importance of considering the absolute or convective character of disturbances, taking gravity into account, to confirm this and present theoretical results on the behaviour of standing waves.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…It was shown by Crapper et al [12] that viscosity does not influence the initial stages of wave development, whilst Lin et al [13] showed that the critical Weber number does not depend on the liquid-gas density ratio or the Reynolds number. [14] provide an explanation of the importance of considering the absolute or convective character of disturbances, taking gravity into account, to confirm this and present theoretical results on the behaviour of standing waves.…”
Section: Introductionsupporting
confidence: 69%
“…The new stability criterion provides an interesting connection to the hypothesis made by De Luca and Meola [14], that in the case of a varying surface tension the constant surface tension in (1) should be replaced by the surface pressure. The two surface pressures, corresponding to the two free surfaces of the curtain, are defined as j = γ s, j − γ j = RT Γ in,1 Γ j , having used the equation of state (16).…”
Section: Stability Criterionmentioning
confidence: 74%
“…Since early studies of Savart [1] and Boussinesq [2], numerous investigations have focused on the formation and stability of liquid curtains [3][4][5][6], which are of some importance for coating techniques, both from fundamental and practical points of view. In most experiments, sheets are obtained by a flow through a slot which induces a jet at its outlet, with slot geometry allowing various sheet shapes [3,[7][8][9].…”
mentioning
confidence: 99%
“…The symmetric waves have a higher growth rate at higher density ratios. Luca and Costa [93] analysed the flow of plane inviscid sheets under the influence of gravity by the asymptotic behavior of a localized perturbation. For antisymmetric disturbances a critical Weber number is found below which the sheet is locally absolutely unstable and above which it is locally convectively unstable.…”
Section: Planar Liquid Sheetsmentioning
confidence: 99%